Enantioselective addition of diphenyl phosphonate to ketimines derived from isatins catalyzed by binaphthyl-modified organocatalysts - Jang, Hee Seung; Kim, Yubin; Kim, Dae Young (Beilstein Journal of Organic Chemistry, 2016)
Chiral binaphthyl-modified squaramide-catalyzed enantioselective addition of diphenyl phosphonate to ketimines derived from isatins has been achieved. This method affords practical and efficient access to chiral 3-amino-3-phosphonyl-substituted oxindole derivatives in high yields with excellent enantioselectivities (up to 99% ee).
Keywords: 3-amino-3-phosphonyl-substituted oxindole; α-aminophosphonates; bifunctional organocatalyst; ketimines; organocatalysis; squaramide

(untitled) - Berlicki, L.; Kafarski, P. (Curr. Org. Chem., 2005)

(untitled) - Kafarski, P.; Lejczak, B. (Curr. Med. Chem., 2001)

(untitled) - Moonen, K.; Laureyn, I.; Stevens, C. V. (Chem. Rev., 2004)

(untitled) - Xu, Y.; Yan, K.; Song, B.; Xu, G.; Yang, S.; Xue, W.; Hu, D.; Lu, P.; Ouyang, G.; Jin, L.; Chen, Z. (Molecules, 2006)

(untitled) - Yao, G.-y.; Ye, M.-y.; Huang, R.-z.; Li, Y.-j.; Pan, Y.-m.; Xu, Q.; Liao, Z.-X.; Wang, H.-s. (Bioorg. Med. Chem. Lett., 2014)

(untitled) - Hu, D.-Y.; Wan, Q.-Q.; Yang, S.; Song, B.-A.; Bhadury, P. S.; Jin, L.-H.; Yan, K.; Liu, F.; Chen, Z.; Xue, W. (J. Agric. Food Chem., 2008)

(untitled) - Hirschmann, R.; Smith, A. B., III; Taylor, C. M.; Benkovic, P. A.; Taylor, S. D.; Yager, K. M.; Sprengeler, P. A.; Benkovic, S. J. (Science, 1994)

(untitled) - Barder, A. (Aldrichimica Acta, 1988)

(untitled) - Mucha, A.; Kafarski, P.; Berlicki, L. (J. Med. Chem., 2011)

(untitled) - Palacios, F.; Alonso, C.; de Los Santos, J. M. (Chem. Rev., 2005)

(untitled) - Gröger, H.; Hammer, B. (Chem. – Eur. J., 2000)
See for a review.

(untitled) - Ordonez, M.; Viveros-Ceballos, J. L.; Cativiela, C.; Azerpe, A. (Curr. Org. Synth., 2012)

(untitled) - Vicario, J.; Ortiz, P.; Ezpeleta, J. M.; Palacios, F. (J. Org. Chem., 2015)

(untitled) - Marti, C.; Carreira, E. M. (Eur. J. Org. Chem., 2003)

(untitled) - Dounay, A. B.; Overman, L. E. (Chem. Rev., 2003)

(untitled) - Trost, B. M.; Brennan, M. K. (Synthesis, 2009)

(untitled) - Liu, Y.; Han, S.-J.; Liu, W.-B.; Stoltz, B. M. (Acc. Chem. Res., 2015)

(untitled) - Galliford, C. V.; Scheidt, K. A. (Angew. Chem., Int. Ed., 2007)

(untitled) - Zhou, F.; Liu, Y.-L.; Zhou, J. (Adv. Synth. Catal., 2010)

(untitled) - Kato, Y.; Furutachi, M.; Chen, Z.; Mitsunuma, H.; Matsunaga, S.; Shibasaki, M. (J. Am. Chem. Soc., 2009)

(untitled) - Tomita, D.; Yamatsugu, K.; Kanai, M.; Shibasaki, M. (J. Am. Chem. Soc., 2009)

(untitled) - Trost, B. M.; Czabaniuk, L. C. (J. Am. Chem. Soc., 2010)

(untitled) - Cheng, L.; Liu, L.; Wang, D.; Chen, Y.-J. (Org. Lett., 2009)

(untitled) - Qian, Z.-Q.; Zhou, F.; Du, T.-P.; Wang, B.-L.; Ding, M.; Zhao, X.-L.; Zhou, J. (Chem. Commun., 2009)

(untitled) - Bui, T.; Hernández-Torres, G.; Milite, C.; Barbas, C. F., III (Org. Lett., 2010)

(untitled) - Mouri, S.; Chen, Z.; Mitsunuma, H.; Furutachi, M.; Matsunaga, S.; Shibasaki, M. (J. Am. Chem. Soc., 2010)

(untitled) - Shen, K.; Liu, X.; Wang, G.; Lin, L.; Feng, X. (Angew. Chem., Int. Ed., 2011)

(untitled) - Montesinos-Magraner, M.; Vila, C.; Cantón, R.; Blay, G.; Fernández, I.; Muñoz, M. C.; Pedro, J. R. (Angew. Chem., Int. Ed., 2015)

(untitled) - Bao, X.; Wang, B.; Cui, L.; Zhu, G.; He, Y.; Qu, J.; Song, Y. (Org. Lett., 2015)

(untitled) - Nakamura, S.; Takahashi, S. (Org. Lett., 2015)

(untitled) - Arai, T.; Tsuchiya, K.; Matsumura, E. (Org. Lett., 2015)

(untitled) - Takada, H.; Kumagai, N.; Shibasaki, M. (Org. Lett., 2015)

(untitled) - Engl, O. D.; Fritz, S. P.; Wennemers, H. (Angew. Chem., Int. Ed., 2015)

(untitled) - Liu, T.; Liu, W.; Li, X.; Peng, F.; Shao, Z. (J. Org. Chem., 2015)

(untitled) - Zhao, J.; Fang, B.; Luo, W.; Hao, X.; Liu, X.; Lin, L.; Feng, X. (Angew. Chem., Int. Ed., 2015)

(untitled) - George, J.; Sridhar, B.; Reddy, B. V. S. (Org. Biomol. Chem., 2014)

(untitled) - Kumar, A.; Sharma, V.; Kaur, J.; Kumar, V.; Mahajan, S.; Kumar, N.; Chimni, S. S. (Tetrahedron, 2014)

(untitled) - Kang, Y. K.; Kim, S. M.; Kim, D. Y. (J. Am. Chem. Soc., 2010)

(untitled) - Kang, Y. K.; Lee, H. J.; Moon, H. W.; Kim, D. Y. (RSC Adv., 2013)

(untitled) - Kang, Y. K.; Kim, D. Y. (Adv. Synth. Catal., 2013)

(untitled) - Kang, Y. K.; Kim, D. Y. (Chem. Commun., 2014)

(untitled) - Suh, C. W.; Woo, S. B.; Kim, D. Y. (Asian J. Org. Chem., 2014)

(untitled) - Suh, C. W.; Kim, D. Y. (Org. Lett., 2014)

(untitled) - Sung, H. J.; Mang, J. Y.; Kim, D. Y. (J. Fluorine Chem., 2015)

(untitled) - Kwon, S. J.; Kim, D. Y. (Chem. Rec., 2016)

(untitled) - Suh, C. W.; Chang, C. W.; Choi, K. W.; Lim, Y. J.; Kim, D. Y. (Tetrahedron Lett., 2013)